Challenges in Law Enforcement Against Online Phishing Fraud from a Positive Law Perspective - Siti Hardianti Rambing; Fenty U. Puluhulawa; Apripari Apripari (The Easta Journal Law and Human Rights, 2026)
The development of information technology has fueled an increase in cybercrime, particularly online fraud through phishing, which poses serious challenges for law enforcement in Indonesia. This study aims to analyze the obstacles to law enforcement against phishing from a positive law perspective and to evaluate the effectiveness of existing regulations. The method used is normative legal research with a legislative and conceptual approach, through a literature review of primary, secondary, and tertiary legal materials. The results of the study indicate that the obstacles to law enforcement are multidimensional, including weaknesses in legal substance that have not adapted to technological developments, limitations in the capacity of law enforcement officials and supporting facilities, as well as low digital literacy among the public. Furthermore, the cross-border nature of the crime and the complexity of digital evidence exacerbate the challenges in law enforcement. This study concludes that an integrative approach is necessary through regulatory reform, institutional capacity building, and strengthened collaboration between the government, the private sector, and the public to achieve effective and responsive law enforcement against phishing crimes.